Deposition-rate dependent kinetic roughening for nanoscale sputter-deposited Cu films on Si surface. (September 2021) - Boscarino, S.; Censabella, M.; Piccitto, G.; Grimaldi, M.G.; Ruffino, F.
Abstract: This work presents an experimental study on the kinetic roughening for nanoscale-thick sputter-deposited Cu films on Si surface. In particular, the Cu films were deposited by using two different deposition rates and their Root-Mean-Square surface roughness was quantified by means of atomic force microscopy measurements. The results of these analyses are discussed on the basis of the dynamic scaling theory and, hence, evaluating the steady growth roughness exponent α and the dynamic growth roughness exponent β. We find a value for α = 0.89 ± 0.07 independent on the Cu deposition rate, while a value of β = 0.23 ± 0.03 at the lower Cu deposition rate (1.7 nm/min) and a value of β = 0.64 ± 0.05 at the higher Cu deposition rate (7.0 nm/min). At the lower deposition rate, the combined values of α = 0.89 ± 0.07 and β = 0.23 ± 0.03 suggest a growth process for the Cu film in thermodynamic equilibrium and dominated by surface diffusion. On the other hand, the combined values of α = 0.89 ± 0.07 and β = 0.64 ± 0.05 suggest a growth process again dominated by surface diffusion however with the occurrence of growing instabilities. Graphical abstract: Image 1 Highlights: Nanoscale-thick Cu films were sputter-deposited on Si substrate by using two different deposition rates. AFM analysis were used to quantify the Cu films surface roughness versus the scan size. AFM analysis were used to quantify the Cu films saturation surface roughness versus the film thickness. The scaling theory of growing interfaces was used to analyze the Cu films roughness behavior. The steady and dynamic growth roughness exponents were quantified.